HUBUNGAN PENGETAHUAN DAN SIKAP KLIEN DENGAN PEMANFAATAN VOLUNTARY COUNSELING TESTING (VCT) PADA KELOMPOK BERISIKO DI PUSKESMAS PADANG BULAN MEDAN - SELLI DOSRIANI SITOPU; JUANDA RIDO ESA NDRURU (LP2MTBM MAKARIOZ, 2018)
Voluntary Counseling Testing (VCT) is one of the strategies to prevent HIV / AIDS preventionconsidered to be quite efficient. To know the status of HIV / AIDS early can be done through VCT servicescomprehensive so that negative consequences that may arise can be prevented from the beginning, and reduceHIV / AIDS morbidity rate. One of the factors that influence individuals to do VCT examinations isbecause of the lack of information about VCT and HIV / AIDS, besides that it was also due to the community's stigma towardssufferers of HIV / AIDS so that clients who have already done an examination are reluctant to visitback. The research objective is to analyze the relationship between knowledge and attitudes of clients with the use of VCTat risk groups in Padang Bulan Medan Health Center. This type of research is an analytical survey withcross sectional approach. The population in the study were all clients who came to visit the VCT Policethere are 359 people. The sample of this study was 79 people and the sampling technique wasaccidental sampling. To analyze relationships using the chi-square test. The results of the study showthe majority of clients have good knowledge, and negative attitudes with the use of VCT are lacking. Test resultsthe relationship between knowledge and utilization of VCT services obtained p value 0.017 (P <0.05) which statedthere is a significant relationship between the knowledge of the client and the use of VCT which means higherclient knowledge about VCT, the utilization of VCT services is getting better. Whereas relationship attitudewith the use of VCT services obtained p. value 0.766, there is no relationship between the attitude of the client andutilization of VCT. It can be proven that even though good knowledge does not produce a positive attitudeutilizing VCT services. It is hoped that the VCT Poly nurses will take a persuasive approachso that risky clients can be positive using VCT. Padang Bulan Agar Health Centermaintain and improve superior VCT services to all patients at risk soefforts to prevent and transmit the HIV virus through VCT service programs are achieved optimally.